Pay-for-performance challenges in family physician program - Gharibi, F (Malays Fam Physician, 2020)
OBJECTIVE: This study was conducted to investigate the challenges faced in the implementation of the pay-for-performance system in Iran's family physician program. STUDY DESIGN: Qualitative. PLACE AND DURATION OF STUDY: The study was conducted with 32 key informants at the family physician program at the Tabriz University of Medical Sciences between May 2018 and June 2018. Method: This is a qualitative study. A purposeful sampling method was used with only one inclusion criterion for participants: five years of experience in the family physician program. The researchers conducted 17 individual and group non-structured interviews and examined participants' perspectives on the challenges faced in the implementation of the pay-for-performance system in the family physician program. Content analysis was conducted on the obtained data. RESULTS: This study identified 7 themes, 14 sub-themes, and 46 items related to the challenges in the implementation of pay-for-performance systems in Iran's family physician program. The main themes are: workload, training, program cultivation, payment, assessment and monitoring, information management, and level of authority. Other sub-challenges were also identified. CONCLUSION: The study results demonstrate some notable challenges faced in the implementation of the pay-for-performance system. This information can be helpful to managers and policymakers.